Anthocyanin profile of elderberry juice: A natural-based bioactive colouring ingredient with potential food application - Silva, Ricardo Fernando Ribeiro (2018)
Elderberry (Sambucus nigra L.) is a widely disseminated plant that produces bright black berries containing high quantities of anthocyanins, acknowledged for their bioactivity and dye capacity. Besides other applications, anthocyanins might be employed as natural colouring agents to reduce/eliminate the use of artificial dyes, while providing positive e ects on consumers’ health. Herein, the anthocyanins profile of elderberry juice was characterised by HPLC-DAD-ESI/MSn. In addition, its antioxidant capacity and cytotoxicity were also evaluated. As a proof-of-concept of its colouring capacity, elderberry juice was added (di erent percentages) to a highly appreciated and consumed pastry product (croissant) and compared with a commercial dye (black carrot). In general, the nutritional properties of control and coloured croissants were similar, despite some individual di erences in sugars and fatty acids. In turn, the appearance obtained with elderberry juice incorporation might be considered innovative, besides partially maintaining the anthocyanins content of fresh juice and showing considerable antioxidant activity.